2012
DOI: 10.1002/mrm.24559
|View full text |Cite
|
Sign up to set email alerts
|

PexLoc—Parallel excitation using local encoding magnetic fields with nonlinear and nonbijective spatial profiles

Abstract: With the recent proposal of using magnetic fields that are nonlinear by design for spatial encoding, new flexibility has been introduced to MR imaging. The new degrees of freedom in shaping the spatially encoding magnetic fields (SEMs) can be used to locally adapt the imaging resolution to features of the imaged object, e.g., anatomical structures, to reduce peripheral nerve stimulation during in vivo experiments or to increase the gradient switching speed by reducing the inductance of the coils producing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…To correct for such effects, many recent studies have focused on measuring these nonlinearities using field probes or preceding measurement scans . As an alternative, several investigators have exploited the nonlinearity of the gradients to their advantage by obtaining curved slices and nonuniform resolution . It has been shown that when nonlinear gradient fields (NLGFs) are used, the adiabatic condition in flow‐driven arterial spin labeling measurements could be achieved with smaller RF pulse amplitudes and as a result, lower SAR values .…”
Section: Introductionmentioning
confidence: 99%
“…To correct for such effects, many recent studies have focused on measuring these nonlinearities using field probes or preceding measurement scans . As an alternative, several investigators have exploited the nonlinearity of the gradients to their advantage by obtaining curved slices and nonuniform resolution . It has been shown that when nonlinear gradient fields (NLGFs) are used, the adiabatic condition in flow‐driven arterial spin labeling measurements could be achieved with smaller RF pulse amplitudes and as a result, lower SAR values .…”
Section: Introductionmentioning
confidence: 99%
“…In specific cases, the intermediate step of calculating and unwrapping ϖ can be skipped and the measured term e i ϖ [divided by e i ϖ( T ) to achieve ϖ( T ) = 0] can be used directly for the pulse calculation. However, in this work, we presented the version with this intermediate step for reasons of descriptiveness and generality (37).…”
Section: Discussionmentioning
confidence: 99%
“…Such concepts arose recently for the purpose of local gradient fields in so‐called PatLoc imaging (40). Also for SSE‐applications this gradient concept bears new potential (37, 41) regarding tailored SEM geometries or enhanced gradient performance. Because in these cases phase modeling by a global k ‐space is not valid anymore (42), phase evolutions have to be given explicitly, e.g., measured spatially resolved by the LPM.…”
Section: Discussionmentioning
confidence: 99%
“…As described in , the design equation for excitation with a small tip angle RF pulse in combination with SEMs including those beyond simple linear gradients is given by: M(boldx)= iγM0(boldx)0T b1(t,x)eiΦ(t,x)dt. The complex transverse magnetization M ⊥ ( x ) generated at position x results from the original magnetization distribution M o ( x ) weighted by the time integral over both the transmitted transverse RF magnetic field b 1 ( t , x ) and the phase Φ( t , x ) accrued from time t up to the end of the SEM time course T , with γ denoting the gyromagnetic ratio. For the sake of clarity, only one RF transmit coil, with homogenous sensitivity, is assumed.…”
Section: Theorymentioning
confidence: 99%